Association of dietary inflammatory index with immune-inflammatory biomarkers in rheumatoid arthritis patients: results from NHANES 1999–2018 - Lu, Zhiming; Xie, Zhiheng; Shen, Kaiwei; Wu, Xunyuan; Feng, Eryou (Frontiers in Nutrition, 2024)
Background: Synovial inflammation is the main reason for joint damage in patients with rheumatoid arthritis (RA). Diet is recognized as one of the therapeutic strategies to control the inflammatory activity in RA. However, few studies have investigated the association between diet and immuneinflammatory biomarkers in RA patients. Our study aims to examine the correlation between dietary inflammatory potential and systemic immune-inflammation Index (SII), neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and lymphocyte-monocyte ratio (LMR) in the RA population.The National Health and Nutrition Examination Survey (NHANES) was the data source utilized in this study, spanning from 1999 to 2018. The study encompassed 2,500 RA participants in total. The dietary inflammatory potential was calculated by the dietary inflammation index (DII) score based on dietary recall interviews. The generalized multiple linear regression analyses were used to evaluate the relationship between DII and immune-inflammatory markers.Furthermore, subgroup analyses and restricted cubic spline models were performed.Results: After full adjustments, there were significant positive correlations between DII levels and SII/NLR in RA patients (SII, β: 14.82, 95% CI: 5.14-24.50, p = 0.003; NLR, β: 0.04, 95% CI: 0.01-0.08, p = 0.005). It was noteworthy that inconsistent results were observed in the association between DII and SII as well as NLR in subgroups of red blood cell levels (Interaction p-value <0.001).Pro-inflammatory dietary status in the RA population is significantly positively correlated with SII and NLR, influenced by variations in red blood cell levels.